PENATALAYANAN GEREJA MENURUT KISAH PARA RASUL 4:32-37 - Firman Panjaitan (Institut Agama Kristen Negeri Kupang, 2021)
Until now in the church there is still ineffective stewardship where only the pastor takes over all aspects of the ministry, due to the lack of understanding of the leaders in coordinating stewardship in the church. Leadership that emphasizes power by leading in an authoritarian way will also have a bad impact on the attitude of subordinates. Unfortunately this is not well understood by the existing churches. Therefore, the writer is moved to research stewardship based on Acts 4-32-37. The method in this research is qualitative with a narrative approach in order to understand the text and context. The results of the study indicate that stewardship based on Acts 4-32-37 indicates a division of duties between leaders and other church members. Leaders must be able to involve church members in good and effective church stewardship. Stewardship has an important role in determining the quality of the congregation. Well-organized stewardship will help leaders to focus on the ministry of the word and testimony, and also encourage church members to help with problems faced by other church members. Acts 4-32-37 proves that good stewardship brings unity of heart and soul and fosters a spirit of caring among the congregation, which gives birth to a prosperous and strong congregation.